2011
DOI: 10.1111/j.1740-8709.2011.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of breastfeeding practices: An analysis of the Sri Lanka Demographic and Health Survey 2006–2007

Abstract: Identification of factors that predict a woman's infant feeding choice is important for breastfeeding promotion programmes. We analysed a subsample of children under 2 years of age from the most recent Sri Lanka Demographic and Health Survey (SLDHS) to assess breastfeeding practices and factors associated with suboptimal practices. SLDHS 2006-2007 used a stratified two-stage cluster sample of ever-married women aged 15-49 years. Breastfeeding indicators were estimated for the last-born children (n = 2735). Sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
90
5
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(118 citation statements)
references
References 26 publications
20
90
5
3
Order By: Relevance
“…11 Neonatal morbidity due to sepsis is attributed to pathogens like viruses, Escherichia coli, Shigella, fungal infections leading to such infections like pneumonia, meningitis, diarrhoea and neonatal sepsis. 10 The findings of the study are consistent with results of a multi-centre study that was conducted in Ghana, Nepal, India and Tanzania which showed a significant association between EBFI and risk of neonatal mortality. In the same study the risk of neonatal deaths was 85% for newborn babies that delayed to initiate breastfeeding beyond 24 hours.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…11 Neonatal morbidity due to sepsis is attributed to pathogens like viruses, Escherichia coli, Shigella, fungal infections leading to such infections like pneumonia, meningitis, diarrhoea and neonatal sepsis. 10 The findings of the study are consistent with results of a multi-centre study that was conducted in Ghana, Nepal, India and Tanzania which showed a significant association between EBFI and risk of neonatal mortality. In the same study the risk of neonatal deaths was 85% for newborn babies that delayed to initiate breastfeeding beyond 24 hours.…”
Section: Discussionsupporting
confidence: 81%
“…9 Similar findings od delayed breastfeeding initiation were recorded in North Central Province of Sri-Lanka, Pakistan, India with initiation rates ranging from 29 to 45%. 10 Findings of the study revealed a significant Pearson Correlation between EBFI and neonatal sepsis at 0.01 levels (2 tailed) at day 3 and day 7. The strong association portrayed in this study between EBFI and neonatal sepsis could be an indicator to the increasing neonatal mortality rate of 29/ 1000 live births with decreased breast feeding initiation rate of 52% in Chipinge district.…”
Section: Discussionmentioning
confidence: 84%
“…Systematic literature review, conducted by Esteves et al 8 indicated that the prevalence of breastfeeding within one hour of birth ranged from 11.4% in one province in Saudi Arabia 9 to 83.3% in Sri Lanka 10 . Data from the 2 nd Research on the Prevalence of Breastfeeding in Brazilian State Capitals and in the Federal District (DF) showed that 67.7% of children breastfed in the first hour of life in the Brazilian cities in 2008 11 .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Hal ini dapat disebabkan beberapa hal misalnya, kondisi post sectio caesarea membuat ibu merasa nyeri dan menjadi sulit untuk menyusui bayinya, keterlambatan untuk melakukan inisiasi menyusui dini dapat menurunkan sekresi prolaktin. 6,7 Tinjauan sistematis yang melibatkan 33 negara mendapatkan hasil bahwa prevalensi menyusui dini lebih rendah pada ibu post sectio caesarea dibandingkan dengan yang melahirkan pervaginam.…”
Section: Departemen Ilmu Kesehatan Masyarakat Kedokteran Pencegahan Funclassified